Modeling hysteresis behavior of sandstone under conditions of slow cyclic loading - V. O. Vakhnenko (Геофизический журнал, 2011)
Simulation of new experimental data on the study of sandstone behaviour under cyclic loading is carried out by use of the recently suggested model. The theoretical and experimental results coincide with reasonable accuracy. It is noted that the models without regard for relaxation mechanism of internal processes are of limited usefulness